Induction of labor with unmedical methods via membrane stripping - Rayya, Marah AbdAlmunim; Hasan, Louai; Aldali, Essam (Journal of medical and pharmaceutical sciences, 2022)
Objective: The aims of this study is to determine the efficacy of membrane stripping for induction of labor in women in term and its role in increasing the rate of vaginal delivery. Collection of samples: Randomized clinical trial was conducted for the period one year (June 2020 –June 2021) at Tishreen University Hospital in Lattakia-Syria. The study included 148 pregnant women in term, and were divided into group (1) included 98 pregnant women who underwent membrane stripping, and group (2) included 50 pregnant women without membrane stripping. Results: The mean age was26.5±5.5 years, without significant differences between the two groups regarding gestational age, obstetric history, and status of cervix. In membrane stripping group, the rate of spontaneous labor was (81.63%), and the response was higher in women with intermediate cervix (89.4%). The rate of vaginal delivery was (85.7%), with low requirement for labor induction (5.1%). On the other hand, in pregnant women group without membrane stripping, the rate of spontaneous labor was (54%), and the response was higher in women with ripe cervix (77.3%). The rate of vaginal delivery was (58%), with high requirement for labor induction (26%). Conclusion: Our study findings suggest that membrane stripping represents a safe and effective procedure for induction of labor and reducing the rate of cesarean delivery especially in the case of intermediate cervix.
Keywords: membrane stripping; induction of labor; vaginal delivery